Topology and shape optimization of structural components with fracture constraints - Wilczyński, Bogdan; Mróz, Zenon (Computer Assisted Methods in Engineering and Science, 2023)
In this paper a numerical design algorithm is described which enables the minimization of the stress intensity factor in a machine component by introducing the defense notch system into the component (weakening of the component) or/and by introducing stiffeners into the component (stiffening of the component) and selection of the shape of its boundary. The paper starts with the extensive review of literature devoted to the optimal design of machine parts with fracture constraints. The design procedure used is the combination of mathematical methods of computer graphics, the Boundary Element Method or the Finite Element Method used for the analysis of the stress field, the sensitivity analysis for the response gradient computations assisted by the Sequential Linear Programming. Also the concept of stop holes drilled at the crack tip, to crack arrest, is discussed. That means replacement of singular stress filed problem (cracks) by quasi-singular one (notches) and optimal design of stop holes becomes notch shape optimization problem.